Polish People’s Republic towards the Conflict in Biafra 1967–1970 - Urbański, Filip (Vade Nobiscum, tom XX/2019: Studia z historii politycznej i wojskowej, 2019)
The article analyzes Poland’s policy on the conflict in Biafra in 1967–1970. The basis for the research are unpublished materials collected in the Archive of the Ministry of Foreign Affairs. According to the author, the Polish diplomacy, maintaining a reserved position on the secession of the Eastern Province of Nigeria and supporting the federal government, was guided by the desire to maintain good political and economic relations. Sustainable politics allowed to take part in the International Observers Group, which contributed to the increase of the prestige of the state on the international arena.